Preserving transaction privacy in bitcoin - Wang, Qin; Qin, Bo; Hu, Jiankun; Xiao, Fu (Future generation computer systems, 2020)
As bitcoin has received considerable attentions, a large number of transactions are increasingly published through the Internet. The potential threat to online transactions is not only limited to the anonymity of identities such as address and pseudonyms, but also other sensitive information shown on scripts like transaction amounts. We propose a framework to hide the amounts by employing the Paillier cryptosystem for encryption and decryption. Due to its homomorphic properties, we create a dumbaccount which can receive the same amounts of bitcoins in each transaction but cannot spend them. This ensures that the hidden amounts are always positive, and keeps the equality between the Input-sum and the Output-sum via the commitment proofs. Our framework achieves delicate anonymity and prevents active and passive attacks, which effectively improves the transaction privacy. Analyses show that our proposal is secure and practical. •We propose encrypted bitcoin transactions allowing coins to be merged, split, or spent while simultaneously keeping the value transferred.•We achieve verifiability of encrypted bitcoin transactions by using Commitment Proof.•We present transaction privacy enhanced bitcoin protocol compatible with the original protocol while only using well established cryptographic assumptions.